The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/s23073622
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Models for Brain Age Prediction Using Six Imaging Modalities on Middle-Aged and Older Adults

Abstract: Machine learning (ML) has transformed neuroimaging research by enabling accurate predictions and feature extraction from large datasets. In this study, we investigate the application of six ML algorithms (Lasso, relevance vector regression, support vector regression, extreme gradient boosting, category boost, and multilayer perceptron) to predict brain age for middle-aged and older adults, which is a crucial area of research in neuroimaging. Despite the plethora of proposed ML models, there is no clear consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Lasso is widely employed in predictive modeling, particularly when dealing with high-dimensional datasets. Prior investigations into brain-age prediction [35,36] have consistently demonstrated the superior performance of the Lasso model when compared to other machine-learning models. Given these compelling findings, we have chosen the Lasso model as the method of choice for brain-age prediction in our study.…”
Section: Brain-age Prediction Modelmentioning
confidence: 95%
“…Lasso is widely employed in predictive modeling, particularly when dealing with high-dimensional datasets. Prior investigations into brain-age prediction [35,36] have consistently demonstrated the superior performance of the Lasso model when compared to other machine-learning models. Given these compelling findings, we have chosen the Lasso model as the method of choice for brain-age prediction in our study.…”
Section: Brain-age Prediction Modelmentioning
confidence: 95%
“…The Lasso (least absolute shrinkage and selection operator) is a regression technique that enhances linear models by penalizing coefficients to prevent overfitting, aiding generalization and variable selection. Its superiority in brain age prediction is welldocumented [34,35]. Hence, we employed the Lasso in our research, with the regularization parameter (alpha) crucial for controlling the penalty magnitude.…”
Section: Brain Age Prediction Modelmentioning
confidence: 99%
“…Dinsdale et al [38] applied a deep 3D convolutional neural network architecture based on the T1 MRI images of 19,687 subjects (age range 44.6 to 80.6 years), achieving MAEs of 2.86 years in females and 3.09 years in males, respectively. In a recent study [39], we conducted a comprehensive comparative analysis of six commonly used machine learning models. Our results revealed that the Lasso model demonstrated significantly superior performance compared to the other five models.…”
Section: Brain Age Prediction Modelmentioning
confidence: 99%